In vitro phosphorylation of plant plasma membrane proteins in response to the proteinase inhibitor inducing factor - Farmer, Edward E. (1989)
A polygalacturonide purified from a tomato leaf pectic polysaccharide that induces the systemic synthesis of proteinase inhibitors in tomato plants enhances the phosphorylation of specific proteins in plasma membrane fractions isolated from tomato and potato leaves. In tomato plasma membranes, two proteins of 34 and 29 kDa show enhanced phosphorylation in response to the polyuronide. In potato plasma membranes, only a protein of 34 kDa exhibited enhanced phosphorylation due to the polyuronide. A noncarbohydrate class of proteinase inhibitor inducing factor, recently identified by workers in this laboratory, resulted in the in vitro hyperphosphorylation of a family of proteins of ≈27 kDa. The phosphorylation of specific polypeptides in leaves in response to the same factors that induce the expression of proteinase inhibitor genes suggests that protein kinases may play an important role in the mechanism of signal transduction leading to defense gene expression.